Impact of active labour market policy programs on employment in the EU during the crisis - Cerar Godec, Lucija (Central European Public Administration Review, 2018)
Due to the financial crisis and the increase in the unemployment rate, active labour market policy (ALMP) inevitably returned to the forefront with its "activation strategy". The research challenge of the article is analysing the effectiveness of ALMP in the period 2007-2013. The methodology of the work is panel regression with fixed effects estimation. The model estimates the effect of the two largest programs of the ALMP, Training and Employment Incentives, on Employment Rate, considering six additional control variables with potential effect on the labour market. The results demonstrate a positive impact of the Training program on the Employment Rate even in the time of crisis. In contrast, the Employment Incentives program had, along with Passive Labour Market Policy (PLMP), a somewhat negative impact on Employment Rate. The findings provide an insight into the nature of ALMP's implementation during the financial crisis. While the training programs keep their active nature, the employment incentives become reactive and to a certain degree act as a measure of PLMP.
Keywords: ekonomska kriza; Evropska unija; nezaposlenost; spodbujanje zaposlovanja; trg dela; usposabljanje